Improved 6-year overall survival in AT/RT: results of the registry study Rhabdoid 2007 - Bartelheim, Kerstin; Dürken, Matthias (Cancer medicine, 2016)
Atypical teratoid rhabdoid tumors (AT/RT) are characterized by mutations and subsequent inactivation of SMARCB1 (INI1, hSNF5), a predilection for very young children and an unfavorable outcome. The European Registry for rhabdoid tumors (EU-RHAB) was established to generate a common European database and to establish a standardized treatment regimen as the basis for phase I/II trials. Thus, genetic analyses, neuropathologic and radiologic diagnoses, and a consensus treatment regimen were prospectively evaluated. From 2005 to 2009, 31 patients with AT/RT from four countries were recruited into the registry study Rhabdoid 2007 and treated with systemic and intraventricular chemotherapy. Eight patients received high-dose chemotherapy, 23 radiotherapy, and 17 maintenance therapy. Reference evaluations were performed in 64% (genetic analyses, FISH, MLPA, sequencing) up to 97% (neuropathology, INI1 stain). Germ-line mutations (GLM) were detected in 6/21 patients. Prolonged overall survival was associated with age above 3 years, radiotherapy and achievement of a complete remission. 6-year overall and event-free survival rates were 46% (±0.10) and 45% (±0.09), respectively. Serious adverse events and one treatment-related death due to insufficiency of a ventriculo peritoneal shunt (VP-shunt) and consecutive herniation were noted. Acquisition of standardized data including reference diagnosis and a standard treatment schedule improved data quality along with a survival benefit. Treatment was feasible with significant but manageable toxicity. Although our analysis is biased due to heterogeneous adherence to therapy, EU-RHAB provides the best available basis for phase I/II clinical trials.